Clinical researchThe association between CBS 844ins68 polymorphism and head and neck squamous cell carcinoma risk – a case-control analysis - Galbiatti, Ana L.S.; Ruiz, Mariangela T.; Raposo, Luis S.; Maniglia, José V.; Pavarino-Bertelli, Erika C.; Goloni-Bertollo, Eny M. (Archives of Medical Science, 2010)
Introduction : Susceptibility to head and neck squamous cell carcinoma may be modified by functional polymorphisms in genes involved in the folate pathway, such as cystathionine beta-synthase (CBS). The CBS 844ins68 polymorphism is associated with DNA methylation changes and cancer development. Material and methods : A case-control retrospective study was conducted in 322 patients with head and neck squamous cell carcinoma and in 531 control subjects without cancer. The polymerase chain reaction-restriction fragment length polymorphism technique was used to genotype the polymorphism. For statistical analysis, 2 test was conducted to examine whether the genotypic frequency of CBS 844ins68 was in Hardy-Weinberg equilibrium and multiple logistic regression was used for comparisons between groups, and for interactions between the polymorphism and risk factors and clinical histopathological parameters. Results : No significant difference in CBS 844ins68 genotypic distribution was observed between the groups. Age > 50 years, male gender and tobacco consumption were predictors of the disease with increased risk of 7.89 (95% CI: 5.56-11.21), 2.49 (95% CI: 1.72-3.62), 6.44 (95% CI: 4.63-8.96) and 2.29 times (95% CI: 1.71-3.06) respectively. There was no association between the distribution of the CBS 844ins68 genotype and risk factors for this disease. According to clinical histopathological parameters, CBS 884ins68 polymorphism presented high frequency in oral cavity (p < 0.05) and patients with the polymorphism presented less survival time (p < 0.05). Conclusions : We concluded that the CBS 844ins68 polymorphism is not associated with HNSCC risk and there is increased risk of this disease in male gender individuals smokers aged over 50 years. In adittion, the polymorphism is more frequent in patients with oral cavity as primary site and in patients with less survival time.